Perancangan Kursi Santai Berbahan Dasar Tempurung Kelapa Untuk Kolam Renang Di Area Tropis Lembab - Gregorius Sanjaya; Adi Santosa; Jean Francois Poilot (Intra, 2018)
In this project, the designer aims to find any alternative materials other than wood because of its excessive usage, which ultimately could dwindle the stock of woods in Indonesia. One of the chosen alternative materials is coconut shell since it is commonly used as charcoal as well as accessories, whereas it could be recycled to be valuable and profitable products. Considering this phenomenon, the designer wants intend to design a furniture made of coconut shells as its main component with regard of shape, construction and aesthetic, which will raise its selling value hereafter. In this process, the designer starts to undertake a research and obtain some information such as its benefits and drawbacks, processing method, etc. by conducting some experiments. With these information, the designer starts to conceptualize the design of lazy chair set, which also serves as a solution to the existing design problem.